The Ability to Use English for Specific Purposes by Hotel Receptionists - Ruslan Hasyim; Rezkiah Hartanti; Muhammad Azwar Assiddiq (Qalam : Jurnal Ilmu Kependidikan, 2021)
This research was exploring the use of English for a specific purpose by hotel receptionists in Sorong city. The data was conducted with quantitative but is not pure students. To collect data, the researchers used instruments such as written tests, questionnaires,s and speaking as instruments. The data was analyzed to descriptive analysis. The result of the study shows that the receptionists’ ability in using English for specific purposes was poor. It was shown by a written test that consisted of technical terms in the hotel. Highest data through an English film, English books. But on the other hand, hotel management never played to improve their English speaking ability, particularly in English coursework, English training, English seminar inside and outside the hotel.